2017
DOI: 10.1155/2017/4909214
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Risk Factors for Salivary Gland Cancer in Canada

Abstract: Aim. To assess the effect of various lifestyle risk factors on the risk of salivary gland cancer in Canada using data from a population-based case-control study. Methods. Data from a population-based case-control study of 132 incident cases of salivary gland cancer and 3076 population controls were collected through self-administered questionnaire and analysed using unconditional logistic regression. Results. Four or more servings/week of processed meat product was associated with an adjusted odds ratio (OR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 42 publications
2
22
1
1
Order By: Relevance
“…Current therapeutic approach to PGT includes surgery (as radical as possible) and radiotherapy [10,11]. As already mentioned, PGT are a group of rare and extremely heterogeneous diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current therapeutic approach to PGT includes surgery (as radical as possible) and radiotherapy [10,11]. As already mentioned, PGT are a group of rare and extremely heterogeneous diseases.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, to date there are no clear recognized risk factors for PGT. A Canadian case-control study suggested that some lifestyle factors (smoking, obesity, alcohol consumption, processed meat and occupational exposure to radiation as well as previous radiation therapy for another head and neck cancer) may contribute to the develop of PGT [10]. Since the rarity of the disease a multidisciplinary treatment approach is mandatory, especially for locally advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Pleomorphic adenoma, a benign tumor of salivary gland origin, is a well‐established risk factor for malignant transformation to carcinoma ex‐pleomorphic adenoma, which has been shown to occur in 3.3%‐8.5% of cases, with the risk of malignant transformation increasing with time . Dietary factors, education level and exercise may play a role but this has yet to be proven . As will be discussed later in this article in connection with clinical trials and targeted therapy, new developments in molecular biology and identification of genetic abnormalities in salivary gland cancer may shed light on the risk factors for salivary gland malignancy.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…[24][25][26] Dietary factors, education level and exercise may play a role but this has yet to be proven. 27 As will be discussed later in this article in connection with clinical trials and targeted therapy, new developments in molecular biology and identification of genetic abnormalities in salivary gland cancer may shed light on the risk factors for salivary gland malignancy.…”
Section: Are There Known Risk Factors For Salivary Gland Tumors?mentioning
confidence: 99%
“…Most of these tumors are benign and might evolve into a malignant form after several years from their initial diagnosis. Previous exposure to irradiation is one of the most common causes of the salivary gland cancers, although viral infection and prolonged chemical usage correlate with a high incidence of glandular tumors [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%